Pesan Dakwah Dalam Lagu Ebiet G. Ade yang Berjudul untuk Kita Renungkan (Analisis Wacana Kritis Van Dijk) - Urwatul Wusqo (Institut Agama Islam Negeri Kendari, 2022)
Along with the development of the times, da'wah activities have experienced significant developments, especially in the media sector, namely that they are no longer only carried out on the pulpit but can be through music. The existence of music that is close to the community makes music an effective alternative medium of propaganda. Based on this, this study wants to see the da'wah messages contained in Ebiet G. Ade's song entitled For Us to Reflect. The type of research used is qualitative by using the literature review method. Van Dijk's critical discourse analysis as an approach in this study is to examine the meaning of a language with the process of meaning production and reproduction. The da'wah message contained in Ebiet G. Ade's song entitled